1967
DOI: 10.1192/bjp.113.496.241
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Vitamin B12 Deficiency in an Elderly Psychiatric Population

Abstract: For many years, cases of pernicious anaemia associated with mental symptoms have been described, and interest in these symptoms was renewed following the introduction of liver therapy (Richardson, 1929; Phillips, 1931). Interest later appeared to decline, so that MacDonald Holmes (1956), almost 20 years after the last important clinical review of the subject, could comment with justification that although the cerebral lesions of pernicious anaemia had been recognized for more than a century they were still muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Thus as regards primary screening of patients for vitamin-B12 deficiency the inspection of the peripheral films was satisfactory. This accords with Shulman's (1967a ;1967b) findings.…”
Section: Discussionsupporting
confidence: 92%
“…Thus as regards primary screening of patients for vitamin-B12 deficiency the inspection of the peripheral films was satisfactory. This accords with Shulman's (1967a ;1967b) findings.…”
Section: Discussionsupporting
confidence: 92%
“…They also observed that liver disease which hindered metabolism might increase the risk of toxicity. Reynolds et al (1966) raised the possibility that psychiatric disorders could be related to the lowered blood folate and vitamin B12 levels, while in a survey Shulman (1967) had found significant lowering of the vitamin B12 level in 8-5 % of 117 psychiatric patients. Strachan & Henderson (1965) had noted the association of mental symptoms with vitamin B12 deficiency even in the absence of anaemia.…”
Section: Psychological Investigations Of Epileptic Patientsmentioning
confidence: 99%
“…Vitamin B 12 therapy had a significant outcome in our cases. Low serum B 12 levels have been reported in resistant schizophrenia [1] and Vitamin B 12 therapy had good outcome in literature [5].…”
Section: /4mentioning
confidence: 99%